Impact of the Financial Crisis on Higher Education in the United States - Geiger, Roger (International Higher Education, 2010)
In the face of the economic crisis of 2008 2009, colleges and universities had to adjust to revenue shortfalls. The decline in endowments influenced especially the wealthiest institutions, which are often leading institutions. States also reduced their funding for public higher education. Enrollment patterns have opted to public, regional, and 2 year institutions. Long-term consequences are the decline of access among low-income students at selective institutions because of tuition increase while less selective institutions might compromise the quality.